Structural and magnetic characterization of a 1D chain of [Co(II)2(μ-aqua)(μ-carboxylate)2] strung cores - Alborés, Pablo (2009)
A novel 1D chain built up from stringing of [Co2(μ-OH 2)(μ-O2CC(CH3)3)2] units with the bridging 2,2′-bipyrimidine ligand has been synthesized and structurally characterized. The chains are well isolated from each other by the bulky tert-butyl groups of the carboxlyates and show an alternating zigzag configuration for the Co(II) metallic centres. DC magnetic measurements show anti-ferromagnetic coupling, Jca.-3 cm-1 between adjacent Co(II) ions along the chain. Noticeably, good data fitting was obtained by means of simple models that neglect any kind of first order orbital contribution to the spin ground state, which is normally observed in Co(II) complexes. These results were further confirmed by broken-symmetry DFT calculations performed on a tetranuclear model emulating the 1D chain structure. Field dependence magnetization measurements show an incipient field-induced energy level crossing at high magnetic field and low temperature (1.8 K).